Effects of Soil Properties on the Accumulation and Bioavailability of Copper in the Orange Growing Soil in Cao Phong, Hoa Binh - Thu, Tran Thi Tuyet; Thi Khanh Ly, Trieu; Thi Hue, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2024)
This study focuses on investigating the crucial influence of some soil properties on the adsorption capacity and fractions of Cu in the citrus-growing soil in Cao Phong district, Hoa Binh province. Batch experiments were conducted by adding 0, 100, 500, and 1000 mgCu/L to soil samples with different characteristics. In the 100 mgCu/L added experiment, we found the highest Cu adsorption rate (> 93.76%) in soil samples with loamy texture, high pH KCl, %OC, and low nutrients. Conversely, the lowest Cu adsorption rates (78.32-79.23%) were observed in soil samples with lower pH, and higher %OC and nutrient availability. Noting that the total adsorbed Cu has a negative correlation with the amount of Cu added to the soil, gradually decreasing from (78.32-95.67%) to (26.67-34.19%) and the lowest (22.48-28.56%) in soil samples with the added levels of 100, 500, and 1000 mgCu/L, respectively. In soil samples with total Cu > 200 mg/kg, pH KCl 4.79-5.32, and OC 1.34-2.06%, the bioavailable Cu ranged from 2.29-4.29 mg/kg, which is safe for the soil environment and ecosystem, and sufficient as a micronutrient for citrus plants. It is necessary to find the best solutions for managing Cu-polluted soils.